From being to becoming: Mapping out the subjective, affective, and temporal 'in-between' in "A History of Violence" - Audette-Longo, Michael (University of Ottawa (Canada), 2009)
While the self is a central figure in the study of Communication, it is generally depicted as an autonomous figure that communicates to connect with others and the world. In this thesis we problematize this instrumental articulation by focussing on the concepts of affect and time. Specifically, we analyze these concepts in the film A History of Violence through the three-tiered methodology of discourse analysis, articulation, and intermediality. By analyzing specific scenes in this film, we demonstrate that affective investments function as a communicative circuit in which the individual becomes 'in-between' the pre-personal and subjective intensities of affect. Concomitant with this circuit is the revelation of multiple temporalities that underpin the present moment of investment. We then conclude that affect and time can help us move from being to becoming by challenging the assumption of autonomous selves, which raises new issues that are pressing to be recognized in Communication Studies.
Keywords: Speech Communication.